2015
DOI: 10.1111/hsc.12297
|View full text |Cite
|
Sign up to set email alerts
|

Understanding carers’ lived experience of stigma: the voice of families with a child on the autism spectrum

Abstract: Existing research suggests that there are several unique challenges associated with caring for a child on the autism spectrum. Despite a growing evidence base regarding autism spectrum disorders and their increasing prevalence, children on the autism spectrum and their families continue to perceive stigmatisation from various sources throughout the community. These perceptions of stigma can profoundly impact the quality of life of these children and their carers alike. This exploratory study sought to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
87
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 33 publications
12
87
1
2
Order By: Relevance
“…Our research supports the findings of other recent studies in Australia (Broady, Stoyles, and Morse 2015), Nepal (Heys et al 2016), Pakistan and India (Minhas et al 2015), China (Lu et al 2015), the USA and Canada (Kinnear et al 2016) that suggest stigma continues to be a significant challenge for many families of children with autism, irrespective of their ethnic and cultural backgrounds. Kinnear et al's (2016) study in North America found that stigma and their child's autism-related behaviours played the largest roles in making parents lives challenging.…”
Section: Discussionsupporting
confidence: 91%
“…Our research supports the findings of other recent studies in Australia (Broady, Stoyles, and Morse 2015), Nepal (Heys et al 2016), Pakistan and India (Minhas et al 2015), China (Lu et al 2015), the USA and Canada (Kinnear et al 2016) that suggest stigma continues to be a significant challenge for many families of children with autism, irrespective of their ethnic and cultural backgrounds. Kinnear et al's (2016) study in North America found that stigma and their child's autism-related behaviours played the largest roles in making parents lives challenging.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with other studies (i.e. Gray, 1993;Gray, 2002;Green, 2003;Green et al, 2005;Broady et al, 2015;Kinnear et al, 2016) that indicated the majority of parents experienced felt stigma. Stigma certainly plays a major and significant role in making lives difficult for parents of children with ASD.…”
Section: Discussionsupporting
confidence: 93%
“…; Broady et al . ), which might cause fathers to socially withdraw and rely on the emotional support of their partners to a greater extent than fathers of children W/OD. Research indicates that fathers of children with ASD heavily rely on the support of their partner over support from friends or extended family (Paynter et al .…”
Section: Discussionmentioning
confidence: 99%